Assessment of the Impact of the Changes in the Situation of the World Markets on the Regional Processes - Yekimova, Kseniya Valeryevna; Savelyeva, Irina Petrovna; Tsalo, Ilya Markovich (Economy of Regions, 2016)
This article describes the issues of the influence of world economy on the development of regional processes. The nature of the dependence of the modern domestic economy on the trends of the world raw material markets is considered. The heterogeneity of the regional processes to the changes of the world environment indicators is revealed. The channels of the influence of the world market trends changes on the regional processes are investigated. The analysis of the world economy indicators has allowed to create a system of basic indicators whose change reflects the tendencies of the world economy. The offered methodological approach to the assessment of the reaction of the regional processes to the changes in the world market trends is based on the economic cycle concept. The methodological tools include the maps of the time shifts allowing to define the time lag of the retardation of the reaction of certain regional processes to the changes in world economy; the model of the evaluation of the influence of the world economy indicators on the regional process, based on the correlation analysis; the differential matrix of the reactions of regional processes to the changes in world market trends, which enables to group them according to the reaction speed and its value. The authors present the fundamental recommendations for the regional processes management based on the world market dynamics analysis. The approbation of the methodological tools was carried out in the terms of the “Consumer prices level changes” and covered the regional process across 83 regions of Russia. They were classified by the speed and the value of the reaction of the consumer prices level to the changes of world market trends. The research has determined the factors and time limits for necessary involvement of regional authorities into the regulation of the consumer prices level. The selection of the implemented method of the direct and indirect regulation of the consumer prices level is substantiated. The developed methodological approach can be applied for the substantiation of preventive management decisions at the regional level.